BeatPain Utah: study protocol for a pragmatic randomised trial examining telehealth strategies to provide non-pharmacologic pain care for persons with chronic low back pain receiving care in federally qualified health centers. Issue 11 (9th November 2022) - Fritz, Julie M; Del Fiol, Guilherme; Gibson, Bryan; Wetter, David W; Solis, Victor; Bennett, Emily; Thackeray, Anne; Goode, Adam; Lundberg, Kelly; Romero, Adrianna; Ford, Isaac; Stevens, Leticia; et al.
Abstract : Introduction: Although evidence-based guidelines recommend non-pharmacologic treatments as first-line care for chronic low back pain (LBP), uptake has been limited, particularly in rural, low-income and ethnically diverse communities. The BeatPain study will evaluate the implementation and compare the effectiveness of two strategies to provide non-pharmacologic treatment for chronic LBP. The study will use telehealth to overcome access barriers for persons receiving care in federally qualified health centres (FQHCs) in the state of Utah. Methods and analysis: BeatPain Utah is a pragmatic randomised clinical trial with a hybrid type I design investigating different strategies to provide non-pharmacologic care for adults with chronic LBP seen in Utah FQHCs. The intervention strategies include a brief pain consult (BPC) and telehealth physical therapy (PT) component provided using either an adaptive or sequenced delivery strategy across two 12-week treatment phases. Interventions are provided via telehealth by centrally located physical therapists. The sequenced delivery strategy provides the BPC, followed by telehealth PT in the first 12 weeks for all patients. The adaptive strategy uses a stepped care approach and provides the BPC in the first 12 weeks and telehealth PT to patients who are non-responders to the BPC component. We will recruit 500 English-speaking or Spanish-speaking participants who will be individually randomised with 1:1 allocation. The primary outcome is the Pain, Enjoyment and General Activity measure of pain impact with secondary outcomes including the additional pain assessment domains specified by the National Institutes (NIH) of Health Helping to End Addiction Long Initiative and implementation measures. Analyses of primary and secondary measures of effectiveness will be performed under longitudinal mixed effect models across assessments at baseline, and at 12, 26 and 52 weeks follow-ups. Ethics and dissemination: Ethics approval for the study was obtained from the University of Utah Institutional Review Board. On completion, study data will be made available in compliance with NIH data sharing policies. Trial registration number: NCT04923334 .